Impact Of Oil Price And Foreign Direct Investment On Carbon Emission In A Developing Country (Journal of Namibian Studies : History Politics Culture, 2023)
Discussion on environmental health has taken center stage in recent times especially for an oil rich country that attracts a huge amount of Foreign Direct Investment (FDI) in that sector. This study therefore investigates the impact of these activities on the environment in order to provide evidence for policymakers. This study therefore analyzed how oil price and FDI impact carbon emission in a developing economy, using an ARDL estimation technique. It was established in this study that a positive relationship exists between oil price, FDI and carbon emission. Hence, a 1% increase in oil price will trigger a 5% increase in carbon emission and a 1% increase in FDI will trigger a 2% increase in carbon emission. The outcome of this study aligns with the EKC hypothesis which posits a positive relationship between the economic variables used and CO2 emission. The study therefore recommends strong environmental protection policies, which will ensure that emissions are reduced whilst achieving continuous economic growth. Reducing carbon emissions in developing countries, especially Nigeria requires a comprehensive strategy that takes into consideration the role of foreign investment. Policymakers should, therefore, involve measures like carbon pricing and rules on industrial emissions that encourage the use of greener manufacturing techniques.